Case Report: A MiT family translocation renal cell carcinoma in the renal pelvis, calyces and upper ureter misdiagnosed as upper tract urothelial carcinoma - Zou, Yuhua; Liu, Linwei; Xie, Xiaojuan; Zhong, Cunzhi; Wang, Qinlin; Yan, Sheng; Liu, Quanliang (Frontiers in Oncology, 2023)
Background: Upper tract urothelial carcinoma (UTUC) is the most common urothelial malignancy in the renal pelvis or ureter. Renal pelvic carcinoma accounts for 90% of all tumours in the renal pelvis, so the mass in the renal pelvis is usually considered a UTUC. Renal cell carcinoma (RCC) in the renal pelvis, calyces and upper ureter is extremely rare, especially MiT family translocation RCC, which makes this case even more uncommon.We report the case of a 54-year-old man had intermittent painless gross haematuria with occasional blood clots and urodynia for 2 years. Contrast-enhanced computed tomography (CT) and magnetic resonance imaging (MRI) scan showed an enlarged left kidney, and a soft tissue mass was seen in the renal pelvis, calyces and upper ureter. The patient's urine-based cytology was positive three times. Due to the severity of the upper ureteral lumen stenosis, we did not perform pathological biopsy during ureteroscopy. In the current case, clinical symptoms, imaging examinations, urine-based cytology, and ureteroscopy were combined to obtain a preoperative diagnosis of UTUC. Therefore, robot-assisted laparoscopic left radical nephroureterectomy and retroperitoneal lymphadenectomy was were performed. Unexpectedly, the patient was pathologically diagnosed with MiT family translocation RCC after surgery. The surgery was uneventful. There was no intestinal tube injury or other complications perioperatively. The postoperative follow-up was satisfactory.MiT family translocation RCC in the renal pelvis, calyces and upper ureter is extremely rare, and can be easily confused with UTUC, resulting in the expansion of surgical scope. Preoperative ureteroscopy and biopsy or tumour punch biopsy should be used to obtain accurate pathology as far as possible, and the selection of correct surgical method is conducive to a good prognosis for patients.